Minimal ovarian hyperstimulation and intrauterine insemination in subfertility analysis of factors that favours its success - Wan Ramli, Wan Mazlina; Abu Ishak, Nurkhairulnisa; Ramli, Roszaman; Awang, Mokhtar; Daraup, Salmi (2018)
A prospective study of couple underwent Minimal Ovarian Hyperstimulation (MOH)and Intrauterine Insemination (IUI) procedure in Hospital Sultanah Nur Zahirah from 1st January 2013 till 30th June 2014. This study accomplished to evaluate the effectiveness of MOH+IUl as foremost option in infertility modalities. The intention is to identify favorable and appropriate factors that impact successful of IUI. Out of total of 211 MOH+IUI cycles, the success pregnancy rates were 9.95%. This study had approved that chances of getting pregnant were high with MOH+IUI methods in female patients with normal BMI, unexplained infertility causal factor, male couples with high sperm morphology count and thick endometrial thickness during IUI procedure. Most of the patient that succeed to conceive had normal BMI about 17.4%compared with the unfortunate group which had had higher BMI; (p=0.001). The endometrial thickness in pregnant group following MOH+IUI was 11.05mm and as compared to unpregnant group 9.85mm; 16.3% (p=005). Causes of infertility had great effect to gain success of conceive. Study show significant different (p=001) whereby the unexplained infertility had higher pregnancy rate. Sperm morphology also had notable influence to achieve successful of pregnancy (p=0.002). Fortunately, no OHSS incidence was reported in this study. Younger age group (20-25 years) had22.2% pregnancy rate, however it was insignificant statistically. The other factors such as duration and type of infertility, sperm count and motility, numbers of cycles attempted, and number of follicles did not show statistically significant in prognosticating successful outcome of MOH+IUI.